2012
DOI: 10.1098/rspa.2012.0342
|View full text |Cite
|
Sign up to set email alerts
|

Weyl geometry and the nonlinear mechanics of distributed point defects

Abstract: The residual stress field of a nonlinear elastic solid with a spherically symmetric distribution of point defects is obtained explicitly using methods from differential geometry. The material manifold of a solid with distributed point defects-where the body is stress-free-is a flat Weyl manifold, i.e. a manifold with an affine connection that has non-metricity with vanishing traceless part, but both its torsion and curvature tensors vanish. Given a spherically symmetric point defect distribution, we construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 41 publications
1
60
0
Order By: Relevance
“…The body being residually stressed means that this 3-manifold, which we call the material manifold, cannot be isometrically embedded in R 3 . This geometric framework is identical to that used for calculating residual stresses in the presence of non-uniform temperature distributions [15], bodies with bulk growth [21] and bodies with distributed defects [22][23][24]. It should also be noted that this approach is general, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body being residually stressed means that this 3-manifold, which we call the material manifold, cannot be isometrically embedded in R 3 . This geometric framework is identical to that used for calculating residual stresses in the presence of non-uniform temperature distributions [15], bodies with bulk growth [21] and bodies with distributed defects [22][23][24]. It should also be noted that this approach is general, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The ambient space is a Riemannian manifold (S, g), and hence the computation of stresses requires a Riemannian material manifold (B, G) and a mapping ϕ : B → S. For example, in the case of non-uniform temperature changes and bulk growth [15,21], one starts with a material metric G that specifies the relaxed distances of the material points. In the case of distributed defects, the material metric is calculated indirectly [22][23][24]. When there are eigenstrains distributed in a body, the material manifold has a metric that explicitly depends on the eigenstrain distribution.…”
Section: (B) Materials Manifold Of a Body With Eigenstrainsmentioning
confidence: 99%
“…[8][9][10]. Inspired by properties of defects in crystalline materials, they suggested to describe defects in continuum by geometric fields such as curvature and torsion tensors.…”
mentioning
confidence: 99%
“…When ∇ is the Levi-Civita connection of G, for example, (B, ∇, G) is reduced to a Riemannian manifold. We briefly review the geometrical machinery needed for the analysis of defective solids; details are given in [7,22,23]. A linear (affine) connection on a manifold B is an operation ∇ : X (B) × X (B) → X (B), where X (B) is the set of vector fields on B, such that ∀X, Y, X 1 , X 2 , Y 1 , Y 2 ∈ X (B), ∀f , f 1 , f 2 ∈ C ∞ (B), ∀a 1 , a 2 ∈ R: (i) Finally, we quantify non-metricity.…”
Section: Non-riemannian Geometries Cartan's Moving Frames and The Nomentioning
confidence: 99%
“…Unfortunately, these geometrical works remained mostly formal with very few stress calculations for distributed defects. Recently, we revisited the geometric theory of solids with distributed defects and showed that it is also suitable for the calculation of stress fields in nonlinear solids with distributed defects by computing explicitly solutions with either dislocations, disclinations or point defects [7,22,23]. To further emphasize the power of such an approach, here we first present the general geometric theory for combined defects and derive from it a general method for semi-inverse problems in anelasticity based on Cartan's moving frames and structural equations.…”
Section: Introductionmentioning
confidence: 99%